Effects of ground heat exchangers with different connection configurations on the heating performance of GSHP systems. (July 2019) - Qi, Di; Pu, Liang; Ma, Zhenjun; Xia, Lei; Li, Yanzhong
Highlights: A numerical model for GHEs was validated against the experimental data. Parallel configuration of GHEs achieved a better heating performance. The heating performance of GSHP increased with the decrease in the fluid flow rate. The effect of GHE connection configuration on the ground temperature was presented. Abstract: The connection configurations of ground heat exchangers (GHEs) have a significant impact on the ground temperature and the performance of ground source heat pump (GSHP) systems. In this paper, the heating performance of a GSHP system implemented in a net zero-energy building with two different GHE connection configurations, including series and parallel connections, was experimentally and numerically investigated. A mathematical model was developed based on ANSYS fluent to analyze the thermal performance of the GHEs and the model was validated against the experimental data. The experimental results showed that the parallel configuration of the GHEs achieved a better heating performance when the mass flow rate was 2.58 kg·s −1, as compared to that of the series configuration. The system heating performance with both series and parallel configurations of the GHEs increased with the decrease in the fluid flow rate under the same heating load condition. The pressure drop between the inlet and outlet of the GHEs with the series configuration was also higher when compared to that with the parallel configuration.